A Value of Trust (Amanah) in Financial Accountability - Yurmaini; Elwardi Hasibuan; Khairil Anshari (SIASAT, 2021)
This research is qualitative research with a phenomenological approach, the first objective of this research is to find out and analyze the perceptions or views of actors (informants) regarding the value of trust in financial accountability. In addition, the second objective is to determine the application of the value of trust in financial accountability including (financial planning, financial management and financial reporting). The research location is Al Washliyah Sibolga College of Economics, where STIE is a high school that has the most students in its region. The data used are primary data (derived from interviews with key informants), and secondary data (derived from interviews with additional informants, books, financial documents, and some literature). Data analysis techniques use data reduction, data presentation, and conclusions and are supported with the help of the NVivo 12 Plus application. The results of this study are that the value of trust is seen or interpreted as a form of effort to maintain commitment. The commitment in question is that campus financial management starting from planning, management to reporting must refer to the book of financial systems and procedures that have been regulated and published by the Al Washliyah organization. One of the applications of the value of trust in financial accountability is that each income is used in accordance with its designation, STIE Al Washliyah Sibolga guarantees that any income or income will not be used unless it is in accordance with its designation and must be reported and can be accounted for.